2018
DOI: 10.3389/fmicb.2018.01060
|View full text |Cite
|
Sign up to set email alerts
|

An Engineered Distant Homolog of Pseudomonas syringae TTSS Effector From Physcomitrella patens Can Act as a Bacterial Virulence Factor

Abstract: Pseudomonas syringae pv. phaseolicola is the causative agent of halo blight in common bean (Phaseolus vulgaris). Similar to other pathogenic gram-negative bacteria, it secrets a set of type III effectors into host cells to subvert defense mechanisms. HopQ1 (for Hrp outer protein Q) is one of these type III effectors contributing to virulence of bacteria. Upon delivery into a plant cell, HopQ1 undergoes phosphorylation, binds host 14-3-3 proteins and suppresses defense-related signaling. Some plants however, ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 29 publications
(46 reference statements)
1
3
0
Order By: Relevance
“…On the other hand, some other fungi‐derived genes might have been recruited by mosses to regulate or counteract the activities of fungi or other microbes, in addition to their roles in other processes. This second possibility is in line with the role of the HLP gene in plant antimicrobial responses (Piechocki et al ., 2018) and supported by similar cases documented in the literature (Chou et al ., 2015; Di Lelio et al ., 2019). For example, endogenous viral DNAs are known to contribute significantly to the immunity of host animals against viral infection (Aswad & Katzourakis, 2012).…”
Section: Are Fungi‐derived Genes Related To Antagonism Towards Fungi supporting
confidence: 84%
See 1 more Smart Citation
“…On the other hand, some other fungi‐derived genes might have been recruited by mosses to regulate or counteract the activities of fungi or other microbes, in addition to their roles in other processes. This second possibility is in line with the role of the HLP gene in plant antimicrobial responses (Piechocki et al ., 2018) and supported by similar cases documented in the literature (Chou et al ., 2015; Di Lelio et al ., 2019). For example, endogenous viral DNAs are known to contribute significantly to the immunity of host animals against viral infection (Aswad & Katzourakis, 2012).…”
Section: Are Fungi‐derived Genes Related To Antagonism Towards Fungi supporting
confidence: 84%
“…HLPs contain an inosine‐uridine nucleoside hydrolase domain and are homologous to the type III secretion system effector HopQ1 of bacterial pathogens (Li et al ., 2013). The HLP in P. patens only shares 24–30% sequence identity with bacterial HopQ1, but it was shown to induce plant immune responses when ectopically expressed in the bacterium Pseudomonas syringae (Piechocki et al ., 2018). This evidence suggests the HLP genes in fungi are probably involved in interactions with host plants.…”
Section: Some Fungi‐derived Genes Are Highly Responsive To Fungal Andmentioning
confidence: 99%
“…HopQ1 was shown to promote bacterial speck disease of tomato and halo blight of bean ( Wei et al., 2007 ; Ferrante et al., 2009 ; Li et al., 2013a ); but it is also produced by P. syringae strains identified as causal agents of recurring epidemics of chestnut or kiwifruit bleeding cankers ( Green et al., 2010 ; Choi et al., 2017 ). Interestingly, our studies ( Piechocki et al., 2018 ) revealed existence of putative HopQ1 homologs in other pathogenic bacteria and fungi but surprisingly also in lower plants and algae, including Aureococcus anophagefferens a dominant species responsible for destructive brown tide blooms ( Gobler and Sunda, 2012 ). HopQ1 – like proteins (HLPs) show overall homology to nucleoside hydrolases, but due to alterations in the predicted catalytic center compared to the consensus sequence were classified as a distinct family ( Piechocki et al., 2018 ).…”
Section: Introductionmentioning
confidence: 82%
“…Interestingly, our studies ( Piechocki et al., 2018 ) revealed existence of putative HopQ1 homologs in other pathogenic bacteria and fungi but surprisingly also in lower plants and algae, including Aureococcus anophagefferens a dominant species responsible for destructive brown tide blooms ( Gobler and Sunda, 2012 ). HopQ1 – like proteins (HLPs) show overall homology to nucleoside hydrolases, but due to alterations in the predicted catalytic center compared to the consensus sequence were classified as a distinct family ( Piechocki et al., 2018 ). HopQ1 was shown to alter purine metabolism and activate cytokinin signaling ( Li et al., 2013b ; Hann et al., 2014 ) whereas recent studies revealed that XopQ, a HopQ1 homolog from Xanthomonas euvesicatoria exerts 2’,3’-cAMP/cGMP phosphodiesterase activity, which is possibly employed by bacteria to hydrolyze signaling molecules produced by a TIR domain of TNL subclass of plant resistance receptors ( Yu et al., 2022 ).…”
Section: Introductionmentioning
confidence: 82%